The Comparison Question Sentences Between Karonese and English Language: Teory X-Bar - Sri Ninta Tarigan; Mulyadi Mulyadi (BIRCU, 2019)
The objective of this study is to find the comparison question sentences between Karonese and English language. The method of this study was Chomsky Theory X bar to discussed the syntax and semantic writes a diagram tree and NP, VP, PP, AP, Adv.P in questions in sentences. It showed that the dominant questions sentences in Karonese use; Wh-Q + NP?. It wrriten 15 times sentences in question. The second position was Wh-Q + NP + C. English has tenses to mention something. It would be different auxiliary when the time in the present, past and future. The second was found that most English questions have the same formula when asking something. The formula used Wh-Q + Aux + S + V + C ? It conclude that there were a different way to arrange questions sentence in Karonese and English language